20.67%‐Efficiency Inorganic CsPbI3 Solar Cells Enabled by Zwitterion Ion Interface Treatment. Issue 2 (18th November 2022) - Zou, Hong; Duan, Yuwei; Yang, Shaomin; Xu, Dongfang; Yang, Lu; Cui, Jian; Zhou, Hui; Wu, Meizi; Wang, Jungang; Lei, Xuruo; Zhang, Na; Liu, Zhike
Abstract: All‐inorganic CsPbI3 perovskite solar cells (PSCs) have been extensively studied due to their high thermal stability and unprecedented rise in power conversion efficiency (PCE). Recently, the champion PCE of CsPbI3 PSCs has reached up to 21%; however, it is still much lower than that of organic–inorganic hybrid PSCs. Interface modification to passivate surface defects and minimize charge recombination and trapping is important to further improve the efficiency of CsPbI3 PSCs. Herein, a new zwitterion ion is deposited at the interface between electron transporting layer (ETL) and perovskite layer to passivate the defects therein. The zwitterion ions can not only passivate oxygen vacancy (VO ) and iodine vacancy (VI ) defects, but also improve the band alignment at the ETL‐perovskite interface. After the interface treatment, the PCE of CsPbI3 device reaches up to 20.67%, which is among the highest values of CsPbI3 PSCs so far. Due to the defect passivation and hydrophobicity improvement, the PCE of optimized device remains 94% of its original value after 800 h storing under ambient condition. These results provide an efficient way to improve the quality of ETL‐perovskite interface by zwitterion ions for achieving high performance inorganic CsPbI3 PSCs. Abstract : Here, a new versatile zwitterion ion is developed, which can passivate both electron transporting layer (ETL) and perovskite, and improve the band alignment at interface, thus the high power conversion efficiencies of 20.67% and 24.62% are achieved in CsPbI3 and FA0.9 Cs0.1 PbI3 solar cells, respectively. This work will provide important guidance for the design of new interface passivators.